2020
DOI: 10.1002/lno.11442
|View full text |Cite|
|
Sign up to set email alerts
|

Multiple drivers of production and particle export in the western tropical North Atlantic

Abstract: To assess the impacts of Amazon River discharge, Saharan dust deposition, N2‐fixation and mixed‐layer deepening on the biological carbon pump, sediment traps were moored from October 2012 to November 2013 at two sites in the western tropical North Atlantic (49°W,12°N/57°W,12°N). Particle exports interpreted along with satellite‐ and Argo‐float data show peak fluxes in biogenic silica (31 mg m−2 d−1) and organic carbon (25 mg m−2 d−1) during the fall of 2013 that were ten to five times higher than any time earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 78 publications
4
15
0
Order By: Relevance
“…Overall, the positive correlation between the UPZspp/LPZspp-CaCO 3 ratio and POC fluxes (Fig. 9d-all sites; Supplementary Table S7) reflects the enhanced coccolith-CaCO 3 production in the upper photic zone linked to higher productivity in shallower nutricline conditions, whether due to geostrophic wind forcing (i.e., sites CB and M1) or to the occurrence of transient surface blooms (site M4; see Guerreiro et al 2017Guerreiro et al , 2019Korte et al 2020).…”
Section: Coccolith-ballastingmentioning
confidence: 97%
See 1 more Smart Citation
“…Overall, the positive correlation between the UPZspp/LPZspp-CaCO 3 ratio and POC fluxes (Fig. 9d-all sites; Supplementary Table S7) reflects the enhanced coccolith-CaCO 3 production in the upper photic zone linked to higher productivity in shallower nutricline conditions, whether due to geostrophic wind forcing (i.e., sites CB and M1) or to the occurrence of transient surface blooms (site M4; see Guerreiro et al 2017Guerreiro et al , 2019Korte et al 2020).…”
Section: Coccolith-ballastingmentioning
confidence: 97%
“…This is also the case for the rare but very large-sized species Scyphosphaera apsteinii, included in the category "others," which produced up to 15 mg m À2 d À1 at site M4 (Supplementary Table S3). Still, and albeit their much lighter and smaller-sized coccoliths, G. flabellatus and F. profunda were the most important Korte et al 2017 andvan der Does et al 2020). The mass flux of unspecified particles (i.e., residual fraction) results from subtracting the weights of biogenic constituents (i.e., CaCO 3 , organic matter and biogenic silica) from the total mass and has been used as a proxy for dust deposition in the Atlantic Ocean (Jickells et al, 1998), including our study area (e.g., Fischer et al 2016;Guerreiro et al 2017;Korte et al 2017).…”
Section: Species Contributionsmentioning
confidence: 98%
“…Particularly relevant is the role of diatoms. While we account for this in our parameterizations, we treat DDAs and normal diatoms the same way, even though DDAs have been hypothesized to be more efficient in this export (Korte et al., 2020). This means that we may tend to underestimate the contribution of DDAs to POM formation and EP.…”
Section: Caveats and Limitationsmentioning
confidence: 99%
“…At the same time, the lower sediment traps tend to show higher fluxes than their upper counterpart during the same year (13M2, 13M4 and 14M4; Figure 3). For the sediment traps at M4, geochemical analyses revealed that lateral input of Amazon‐River sediments to the upper trap is minimal, if not absent (Van der Does, Pourmand, et al., 2018), while the lower trap at 13M5 was affected by downslope transport of sediment re‐suspended from the nearby Barbados margin, causing much higher deposition fluxes than expected for the overall downwind decreasing trend, including the large outlier in April 2013 (Figure 3; Korte et al., 2020).…”
Section: Resultsmentioning
confidence: 99%